Downregulated MicroRNA-327 Attenuates Oxidative Stress–Mediated Myocardial Ischemia Reperfusion Injury Through Regulating the FGF10/Akt/Nrf2 Signaling Pathway - Zheng, Tao; Yang, Jun; Zhang, Jing; Yang, Chaojun; Fan, Zhixing; Li, Qi; Zhai, Yuhong; Liu, Haiyin; Yang, Jian (Frontiers in Pharmacology, 2021)
Although miR-327 put protective effect on cardiomyocytes as described previously, the potential mechanism still needs further exploration. The aim of this study is to investigate the role and mechanism of miR-327 on oxidative stress in myocardial ischemia/reperfusion injury(MI/RI) process. Oxidative stress and cardiomyocytes injury were detected in rats model of MI/RI, the hypoxia/reoxygenation (H/R) and tert-Butyl hydroperoxide(TBHP) model of H9c2 cells. In vitro, down-regulation of miR-327 inhibited both H/R and TBHP induced oxidative stress, ancd suppressed apoptosis. Meanwhile, fibroblast growth factor 10(FGF10) was enhanced by miR-327 knocked down, followed with activation of PI3K, p-Akt and the translocation of Nrf2. Whereas, miR-327 overexpression performed with an opposite effects. Consistent with the results in vitro, down-regulation of miR-327 attenuated reactive oxygen species(ROS) generation and I/R injury. In a conclusion, inhibition of miR-327 could improve antioxidative ability and myocardial cell survival via regulating FGF10/Akt/Nrf2 pathway.